A novel Sphingobacterium sp. RB, a rhizosphere isolate degrading para-nitrophenol with substrate specificity towards nitrotoluenes and nitroanilines. Issue 14 (26th July 2019) - Samson, Rachel; Bodade, Ragini; Zinjarde, Smita; Kutty, Razia
ABSTRACT: Sphingobacterium sp. RB, a novel bacterial strain isolated from a soil sample, was able to utilize para -nitrophenol (PNP) as sole source of carbon and energy at high concentrations (1.0–5.0 mM). The culture completely degraded 3.0 mM PNP within 36 h with proportionate increase in biomass. With 5.0 mM PNP (700 ppm), 70% degradation was observed within 72 h of incubation. Scanning electron microscope images of the isolate in the presence and absence of PNP showed no significant morphological variations. Liquid chromatography–mass spectrometry analysis indicated that the biodegradation of PNP in this bacterium proceeded via the formation of 1, 2, 4-benzenetriol. Cells previously exposed to PNP (induced) were 30% more effective in degrading PNP. With catechol and phenol, such induction was not observed. Uninduced cells of Sphingobacterium sp. RB were capable of degrading a variety of other nitroaromatic compounds, including 2-nitroaniline, 2, 4-dinitroaniline, 2-nitrotoluene, 3-nitrotoluene and 2, 4-dinitrophenol, within 72 h, thus proving its candidacy as a potent bioremediation agent. To the best of our knowledge, this is the first report on a Sphingobacterium species degrading PNP via formation of 1, 2, 4-benzenetriol. Abstract : This study envisages isolation and characterization of a novel bacterium (identified as Sphingobacterium sp. RB) capable of degrading high concentrations (5.0 mM) of para -nitrophenol, identification of major metabolites involved in para -nitrophenol degradation, determining the effect of inducers on para -nitrophenol degradation and exploration of this isolate to degrade related nitroaromatic compounds such as 2-nitroaniline, 2, 4-dinitroaniline, 2, 4-dinitrophenol, 2-nitrotoluene and 3-nitrotoluene.